Numerical modeling of tides in the late Pennsylvanian Midcontinent seaway of North America with implications for hydrography and sedimentation - Wells,MR; Allison,PA; Piggott,MD; Gorman,GJ; Hampson,GJ; Pain,CC; Fang,F (JOURNAL OF SEDIMENTARY RESEARCH, 2007)
A novel numerical model (the Imperial College Ocean Model, ICOM) is used to simulate tidal circulation in shallow epicontinental seas connected to large, open oceans. ICOM is validated using the present-day North Sea and applied to predict tidal range in the late Pennsylvanian Midcontinent Seaway (LPMS) of North America. The model simulates the effect of the principal tidal constituents (astronomical tides) as well as the tide propagating from the adjacent open ocean (co- oscillating tide). Two ‘‘base-case’’ Pennsylvanian paleogeographies were tested: (1) a maximum sea-level highstand and (2) the early stages of a transgression. Sensitivity tests determined the importance of paleo-water depth and coastline uncertainty on the prediction of tidal range. During the highstand, tidal ranges in the craton interior (Midcontinent Shelf, Illinois and Appalachian basins) are consistently predicted as microtidal (, 2 m tidal range). Such low tidal ranges would have inhibited water-body mixing in the LPMS, promoting stratification. This, combined with the influx of oxygen-poor water from the Permian Basin to the west and high organic input from tropical rivers, may have contributed to the deposition of ‘‘core’’ black shales in LPMS cyclothems. Conversely, a mesotidal to macrotidal diurnal (once-daily tide) regime is predicted for the early transgression in a large-scale embayment in eastern Kansas due to resonant amplification of diurnal tidal constituents. Pennsylvanian strata here have been ascribed to a mesotidal to macrotidal setting and include cyclic rhythmites that suggest a strongly diurnal system, as predicted by ICOM.